2006
DOI: 10.1002/adma.200501210
|View full text |Cite
|
Sign up to set email alerts
|

Ultraporous Nanosheath Materials by Layer‐by‐Layer Deposition onto Co‐continuous Polymer‐Blend Templates

Abstract: Porous polymer materials with interconnected porosity have recently received great attention due to their wide range of possible applications and the challenges they pose in preparation. Their potential applications range from use in the biomedical and pharmaceutical fields (tissue engineering and drug delivery) [1][2][3] to chromatographic materials, [4] to catalysis of chemical and biochemical reactions, [5] and to electronic devices.[6] For tissue-engineering applications, for instance, at least four differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 32 publications
(39 reference statements)
5
41
0
Order By: Relevance
“…Therefore, the PLA/ PCL blend materials have received much attention in recent years. [3][4][5][6][7][8][9][10][11][12] However, most polymer pairs are immiscible thermodynamically because of their unfavorable interactions, including PLA and PCL. The macrophase separation and the poor interfacial adhesion, as a result, highly restrict property combinations between PLA and PCL in their blend.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the PLA/ PCL blend materials have received much attention in recent years. [3][4][5][6][7][8][9][10][11][12] However, most polymer pairs are immiscible thermodynamically because of their unfavorable interactions, including PLA and PCL. The macrophase separation and the poor interfacial adhesion, as a result, highly restrict property combinations between PLA and PCL in their blend.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the LbL technique has attracted tremendous attention for its simplicity, universality and precise control of thickness at the nanoscale, and has been widely applied in various promising research areas, including chemical sensors and biosensors [4] , stimuli-responsive micelles [5] , enzyme immobilization [6] , surface patterning [7][8][9] , controlled drug release systems [10] , photoelectrochemically active electrodes [11] , separation membranes [12] , microporous films [13] , surface-imprinted multilayers [14] , erasable films [15,16] and even macroscopic supramolecular assembly [17] . However, LbL assembled multilayers have been traditionally fabricated based on the weak electrostatic attraction of the interlayers [18][19][20] and the driving force of supramolecular interactions or other weak intermolecular interactions, which are unstable in some rigorous situations, such as high/low pH values, high ionic strength conditions or solutions with disturbances, for example under sonication [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Sarazin et al (2003;2004) developed a novel method for the generation of ultra-porous scaffolds by melt blending 2 or 4 immiscible polymers (Virgilio et al, 2010). Roy et al (2006) deposited polymer/ protein layers onto scaffold surfaces to increase the porosity of the materials. Virgilio et al (2005; and Horiuchi et al (1997) reported partial wetting in a significant number of scaffolds generated by ternary immiscible polymers blends.…”
Section: Introductionmentioning
confidence: 99%